Basic Water Treatment (6th Edition) - Binnie, Chris; Kimber, Martin; Thomas, Hugh (ICE Publishing, 2018)
The Sixth Edition of this book is an accessible and practical guide to all aspects of potable water quality and treatment. Focusing on the issues of most interest to practising engineers, it provides examples of good practice, summarises key issues and criteria, and includes additional theory to explain and support the treatment processes considered. This new edition has been fully updated and has also been expanded to cover additional processes and topics, and to take account of developing concerns relating to emerging contaminants. It includes new chapters on activated carbon adsorption and water re-use to reflect the increasing importance of these subjects, and significant updates to sections on disinfection, emerging contaminants, membrane processes, desalination and advanced oxidation processes. This book is an essential resource for water engineers at all levels - a textbook for students, a handbook for engineers or chemists who are new to the industry, and an indispensable guide full of updated practical information for the established practitioner.